Pediatric Hyperacute Arterial Ischemic Stroke Pathways at Canadian Tertiary Care Hospitals. (11th November 2021) - Gladkikh, Maria; McMillan, Hugh J.; Andrade, Andrea; Boelman, Cyrus; Bhathal, Ishvinder; Mailo, Janette; Mineyko, Aleksandra; Moharir, Mahendranath; Perreault, Sébastien; Smith, Jonathan; Pohl, Daniela
ABSTRACT: Background: Childhood acute arterial ischemic stroke (AIS) is diagnosed at a median of 23 hours post-symptom onset, delaying treatment. Pediatric stroke pathways can expedite diagnosis. Our goal was to understand the similarities and differences between Canadian pediatric stroke protocols with the aim of optimizing AIS management. Methods: We contacted neurologists at all 16 Canadian pediatric hospitals regarding AIS management. Established protocols were analyzed for similarities and differences in eight domains. Results: Response rate was 100%. Seven (44%) centers have an established AIS protocol and two (13%) have a protocol under development. Seven centers do not have a protocol; two redirect patients to adult neurology, five rely on a case-by-case approach for management. Analysis of the seven protocols revealed differences in: 1) IV-tPA dosage: age-dependent 0.75–0.9 mg/kg ( N = 1) versus age-independent 0.9 mg/kg ( N = 6), with maximum doses of 75 mg ( N = 1) or 90 mg ( N = 6); 2) IV-tPA lower age cut-off: 2 years ( N = 5) versus 3 or 10 years (each N = 1); 3) IV-tPA exclusion criteria: PedNIHSS score <4 ( N = 3), <5 ( N = 1), <6 ( N = 3); 4) first choice of pre-treatment neuroimaging: computed tomography (CT) ( N = 3), magnetic resonance imaging (MRI) ( N = 2) or either ( N = 2); 5) intra-arterial tPA use ( N = 3) and; 6) mechanical thrombectomy timeframe: <6 hour ( N = 3), <24 hour ( N = 2), unspecified ( N = 2). Conclusions: Although 44% of Canadian pediatric hospitals have established AIS management pathways, several differences remain among centers. Some criteria (dosage, imaging) reflect adult AIS literature. Canadian expert consensus regarding IV-tPA and endovascular treatment should be established to standardize and implement AIS protocols across Canada.